Spray‐Flame‐Synthesized LaCo1−xFexO3 Perovskite Nanoparticles as Electrocatalysts for Water and Ethanol Oxidation. Issue 16 (21st March 2019) - Alkan, Baris; Cychy, Steffen; Varhade, Swapnil; Muhler, Martin; Schulz, Christof; Schuhmann, Wolfgang; Wiggers, Hartmut; Andronescu, Corina
Abstract: Coupling electrochemical generation of hydrogen with the concomitant formation of an industrially valuable product at the anode instead of oxygen can balance the high costs usually associated with water electrolysis. We report the synthesis of a variety of nanoparticulate LaCo1− x Fe x O3 perovskite materials through a specifically optimized spray‐flame nanoparticle synthesis method, using different ratios of La, Co, and Fe precursor compounds. Structural characterization of the resulting materials by XRD, TEM, FTIR, and XPS analysis revealed the formation of mainly perovskite‐type materials. The electrocatalytic performance of the formed perovskite‐type materials towards the oxygen evolution reaction and the ethanol oxidation reaction was investigated by using rotating disk electrode voltammetry. An increased Fe content in the precursor mixture leads to a decrease in the electrocatalytic activity of the nanoparticles. The selectivity towards alcohol oxidation in alkaline media was assessed by using the ethanol oxidation reaction as a model reaction. Operando electrochemistry/ATR‐IR spectroscopy results reveal that acetate and acetaldehyde are the final products, depending on the catalyst composition as well as on the applied potential. Abstract : Spray‐flame synthesized LaCo1−x Fex O3 perovskites show promising electrocatalytic activity towards the oxygen evolution reaction and ethanol electrooxidation. The selectivity of the ethanol oxidation reaction is influenced by the Fe content, with acetic aldehyde being detected on Fe rich perovskites while acetate is generated on the Fe‐free catalysts up to potentials of 1.7 V vs. RHE.